Assessment Of Lead Content In Soil Samples Obtained From Four Different Sites Of Kabwe, Central Province Of Zambia - Ellah ZINGANI; Gabriel NDHLOVU; Brian Chanda CHILUBA (International Journal of Environmental, Sustainability, and Social Science, 2020)
Pollution has increased soil lead levels to several thousand parts per million; the primary cause of soil lead contamination in Kabwe district is the weathering from the former Zinc-lead mine. Soil lead is a health risk when directly ingested or inhaled as and it is of particular concern for children less than 6 years because of its implication on their growth. Hence this study set out to assess the lead soil content in four different sites of Kabwe district, Central province of Zambia. Literature was reviewed from studies that covered soil lead contamination. A quantitative analytical study was carried out, and it involved geographical mapping of four different sites the north, South, East, and West of Kabwe district which were conveniently selected to collect soil Samples which were taken to The University of Zambia School of Mines, Geology Engineering Laboratory to determine the Levels of soil Lead content using a technique called Geo-Chemical Analysis. The results suggest that the Chowa area is highly polluted with lead metal according to the globally recommended WHO guidelines and Zambia Environmental Management Agency, which all states that Residential areas should not exceed 400Kg/mg or parts per million.